2016
DOI: 10.1002/anie.201606099
|View full text |Cite
|
Sign up to set email alerts
|

Coke Formation in a Zeolite Crystal During the Methanol‐to‐Hydrocarbons Reaction as Studied with Atom Probe Tomography

Abstract: Understanding the formation of carbon deposits in zeolites is vital to developing new,s uperior materials for various applications,i ncluding oil and gas conversion processes.H erein, atom probe tomography (APT) has been used to spatially resolve the 3D compositional changes at the subnm length scale in as ingle zeolite ZSM-5 crystal, whichh as been partially deactivated by the methanol-to-hydrocarbons reaction using 13 C-labeled methanol. The results reveal the formation of coke in agglomerates that span leng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
86
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 80 publications
(90 citation statements)
references
References 31 publications
3
86
0
1
Order By: Relevance
“…In another recent work by J. E. Schmidt et al . C 13 clusters were noted to be present in low Si/Al ratio regions (or high Al concentration regions) after 90 minutes of methanol-hydrocarbon conversion reaction35. Based on our APT results, we also observed a non-uniform distribution of Al in as-prepared HZSM-5 as revealed by the 2D ion concentration map in Fig.…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…In another recent work by J. E. Schmidt et al . C 13 clusters were noted to be present in low Si/Al ratio regions (or high Al concentration regions) after 90 minutes of methanol-hydrocarbon conversion reaction35. Based on our APT results, we also observed a non-uniform distribution of Al in as-prepared HZSM-5 as revealed by the 2D ion concentration map in Fig.…”
Section: Resultssupporting
confidence: 65%
“…More recently work by Schmidt et al . analyzed spatial correlation of C 13 clusters formed in ZSM-5 catalyst particles after 90 minute C 13 isotopically labeled methanol to hydrocarbon conversion reaction35. In their work, based on APT analysis, authors indicated formation of early C 13 clusters which appeared to correlate with regions of high Al content in ZSM particles.…”
mentioning
confidence: 99%
“…After STXM measurements, a needle shaped specimen was carefully removed from the cross section using Ga FIB milling and then studied with APT using the LEAP 4000XR local electrode atom probe equipped with laser pulsing capabilities and an energy compensating reflectron lens and data analysis was performed using CAMECA's IVAS software. We have previously reported both in detail ,,,. The APT experiment was performed on a tungsten wire instead of a Si micropost array, which is the more historical method of conducting APT experiments …”
Section: Methodsmentioning
confidence: 99%
“…Recently, the first use of atom probe tomography (APT) to investigate the 3-D distribution of elements in zeolites at the subnm scale has been reported. 108,109 In 2016 Schmidt et al used APT to study coke formation and its relation to inhomogeneous Al distribution in large ZSM-5 crystals after MTH (using 13 C-labelled methanol to distinguish the formed coke species from contaminations). 109 APT samples were taken from the (Al rich) surface and the (Al poor) core of the ZSM-5 crystal showing a clear correlation of coke formation and Brønsted acid site density.…”
Section: Impact Of Acidity On Stability and Product Selectivitymentioning
confidence: 99%